2004
DOI: 10.1111/j.1471-6712.2004.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and chronic daily headache management: a qualitative study of patients’ perceptions

Abstract: Health care is changing towards a greater involvement of the patients in their own care. Therefore, it is important to increase understanding of the patients' perspective of chronic diseases, including migraine and CDH. The results from this study inform health care professionals of the range of their patients' needs and preferences. This knowledge can be used to shape clinical practice, to develop patient education programmes and to further research efforts into issues that are important to the headache patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 28 publications
8
70
0
Order By: Relevance
“…The invisibility of the disorder and the feeling of being doubted about whether one was really being afflicted with migraine further complicates life. The knowledge provided by the research presented here adds a new perspective revealing the deep meaning of living with migraine, and it can be seen as a complement to existing research, which has pointed out the impact migraine has on life [20-22] as well as on the strategies adopted to manage it [16-19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The invisibility of the disorder and the feeling of being doubted about whether one was really being afflicted with migraine further complicates life. The knowledge provided by the research presented here adds a new perspective revealing the deep meaning of living with migraine, and it can be seen as a complement to existing research, which has pointed out the impact migraine has on life [20-22] as well as on the strategies adopted to manage it [16-19]. …”
Section: Discussionmentioning
confidence: 99%
“…Persons with migraine manage their illness in a highly individual way and predominantly, use the traditional medical system, generally taking the form of prescription drugs [16]. The way they choose to manage their migraine was impacted by their own perceptions of their disability and even though those afflicted with migraine perceived it to be a serious problem, they viewed their illness as a less serious health issue than some others have to face [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors describe actions and cognitive strategies in dealing with various chronic disorders, and discuss how patients are making life adjustments to cope with their ailment, with regard to a focus on experience and control over their life and their disorders [10,20 Á/22]. Studies in self-management of diseases reveal that utilizing one's own resources has a marked effect on the perception of one's disease and provides tools to handle one's disease [6]. Penzien et al [23] present a review of the use of cognitive and behavioural strategies in patients with tension-type headache.…”
Section: Can the Strategies Presented Here Be Recommended?mentioning
confidence: 99%
“…Even so, tension-type headache presenting with subjective symptoms without objective findings is still not fully understood in medical terms. Peters et al found that headache sufferers adapted symptom management to suit their needs and preferences in an individual style [5,6]. Use of healthcare, medication, and alternative therapies constituted only a limited part of their coping strategies.…”
mentioning
confidence: 99%
“…Assessing migraine severity, disability, quality of life and medication responses has been the focus of recent studies [1][2][3][4][5][6][7][8]. Migraineurs' expectations have been well studied and defined, but only for the acute attack [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%